Pengaruh Komunikasi Kerja Dan Komitmen Organisasi Terhadap Kinerja Pegawai Tetap Non Pegawai Negeri Sipil Di Rumah Sakit Umum Pusatprof. Dr. I.G.N.G. Ngoerah - Merta I Ketu; Agus Sudika I Wayan; Yusnimi Ni Made (Departement of Mathematics Education, 2024)
This research took the research object at the Prof. Ngoerah Central General Hospital with the aim of analyzing the influence of Work Communication, Organizational Commitment on the Performance of Non-Civil Servant (PNS) employees using the grand theory of Management of State Civil Apparatus Law of the Republic of Indonesia Number 5 of 2014, supporting Organizational behavior management theory. This research uses quantitative methods, questionnaires with sampling samples and the Slovin formula with four hypotheses. This research found: 1. Work Communication has a positive and significant effect on the Performance of Permanent Non-Civil Servant (PNS) Employees at Prof Ngoerah Central General Hospital 2. Work Communication has a significant positive effect on the Performance of Permanent Non-Civil Servant (PNS) Employees at Home Prof Ngoerah Central General Hospital, 3. Organizational Commitment has a positive and insignificant effect on the Performance of Permanent Non Civil Servant Employees (PNS) at the Central General Hospital Prof Ngoerah, 4. Organizational Commitment does not mediate work communication on the Performance of Permanent Non Civil Servant Employees (PNS) at Prof Ngoerah Central General Hospital. The implications of this research contribute simultaneously to Prof.Central General Hospital. Ngoerah, this research also found that Organizational Commitment has an insignificant effect so it is necessary to carry out further research.